Peran Gerakan Masjid dalam Program Sejahterakan Petani Sayur di Tengah Anjloknya Harga Pasar: Studi Kasus Masjid Nurul Ashri Yogyakarta - Andira Nurqalbi; Novinta Sari; A. Indri Wahyuni; Syarif Hidayatullah; Tri Amal Nazar Saputro (Institut Muslim Cendekia, 2025)
In a situation where market price fluctuations often harm vegetable farmers, a fair and sustainable empowerment model is needed. This study examines the role of the Nurul Ashri Mosque Movement in Yogyakarta in the Vegetable Farmer Welfare Program as a form of religious community participation in responding to the economic crisis faced by farmers. The research approach is qualitative, employing a case study method, utilizing in-depth interviews, participatory observation, and documentation. The results indicate that the mosque serves as an initiator and facilitator in the direct distribution of harvest produce from farmers to consumers through schemes such as jastip (direct delivery), free vegetable bazaars, and distribution to institutions. This program not only improves farmers' welfare but also revives the social function of mosques as centers of community activity. The novelty of this research lies in the integration of religious values with a community economic approach, strengthening social solidarity. Mosques have proven to be strategic actors in inclusive and equitable local economic development.